Coaches of youth field sports as delivery agents of injury prevention programmes: how are we training the trainers? A scoping review - Guilfoyle, L.; Kenny, I. C.; O'Sullivan, K.; Campbell, M. J.; Warrington, G. D.; Glynn, L. G.; Comyns, T. (British Journal of Sports Medicine, 2024)
Objective To systematically map the coach education (CE) component of injury prevention programmes (IPPs) for youth field sports by identifying and synthesising the design, content and facilitation strategies used to address competency drivers and behaviour change.